Phytochemical Analysis of Leaves and Cherries of Coffee and Sensory Evaluation of Tea Products of Robusta Coffee in Songkhla, Thailand - Yudithia Maxiselly; Pisamai Anusornwanit; Adirek Rugkong; Rawee Chiarawipa (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2022)
The research attempts to analyze the phytochemical compositions of both the leaves and the cherries of coffee and examine preference through the sensory evaluation of consumers consuming tea products of Robusta coffee from Songkhla, Thailand. The methods used for the phytochemical analysis were conducting an antioxidant content analysis using the Ferric ion reducing antioxidant power method, conducting total phenolic and tannin contents analysis using the Folin-Ciocalteau method, and conducting a total flavonoid content measurement using the aluminum chloride colorimetry method. For the sensory evaluation of tea products (leaves and cherries of coffee), a set of questionnaires was used as the survey observation tools to collect the data from consumers at some coffee and tea shops. The data analysis was using T-test for phytochemical composition and F-test on sensory evaluation. This study shows that Robusta coffee leaves and cherries contained phytochemical compounds of different values. Compared to the cherries, the leaves had higher values of phytochemical compositions. Based on the sensory evaluation of consumers, tea products made from leaves and cherries were highly rated. Coffee cherry tea demonstrated a higher percentage of interest compared with coffee leaf tea.